Impact of Ekman Pumping on the Meridional Coherence of the AMOC - Neil J. Fraser; Alan D. Fox; Stuart A. Cunningham (Geophysical Research Letters)
Abstract The effect of wind‐induced vertical velocity on the meridional coherence of Atlantic meridional overtuning circulation (AMOC) is examined using theory, observations, and a numerical model. Two cases are considered: (a) the AMOC computed in depth coordinates and (b) the AMOC computed in isopycnal coordinates. In depth space, the difference between the AMOC at different latitudes is largely explained by vertical transport across the 1000m depth surface induced by Ekman pumping. In density space, this difference is explained by Ekman‐driven heave of the neutral surface separating the upper and lower limbs. This adiabatic “sloshing” changes the relative volumes of the upper and lower AMOC limbs, obscuring the distribution and advection of the diapycnal transports which characterize the AMOC.